2014
DOI: 10.1515/chem-2015-0054
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electrode material on hydrogen peroxide generation by DC pinhole discharge

Abstract: Abstract:In this work, several materials were studied as electrodes in a pinhole configuration of a DC plasma discharge to estimate their effect on the efficiency of the discharge, indicated by hydrogen peroxide production. Detection was carried out using a specific titanium reagent. This was combined with ICP-OES analysis of the final solutions to determine the difference between the amount of electrode material released during the discharge operation and electrolysis experiment carried out under the same con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…(3)) cannot be ruled out. To test this possibility, the carbon cathode was replaced by a stainless steel cathode that has a lower activity for the electrochemical production of H 2 O 2 than a graphite rod [39]. However, in spite of a significant reduction in the rate of H 2 O 2 formation on the stainless steel cathode, the concomitant degradation of BPA was only slightly reduced compared to case of graphite rod cathode (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(3)) cannot be ruled out. To test this possibility, the carbon cathode was replaced by a stainless steel cathode that has a lower activity for the electrochemical production of H 2 O 2 than a graphite rod [39]. However, in spite of a significant reduction in the rate of H 2 O 2 formation on the stainless steel cathode, the concomitant degradation of BPA was only slightly reduced compared to case of graphite rod cathode (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The plasma-ethanol interface is also known to produce radicals leading to the formation of hydrogen peroxide (H 2 O 2 ) [52,53,61] and we have confirmed that also in our case H 2 O 2 is produced and consumed by equation (3) (see Supporting Information). [62] The interaction of locally produced (i.e., close to the interface) H 2 O 2 with reduced copper atoms then leads to the formation of CuO, [63,64] where the very high reaction rates of solvated electrons and the non-acidic state (>6 pH; measured before and after synthesis, see Supporting Information) prevents Fentonlike reactions with the Cu-ions. [51,65] The size of the NPs is then determined by the local concentration of coalescing CuO.…”
Section: Resultsmentioning
confidence: 99%
“…Aluminium was quite easily sputtered by the discharge, but it had been reported that this element did not decrease the hydrogen peroxide formation a lot [21]. The second electrode material, which we used in experiments presented in this paper, was platinum which was not sputtered so rapidly, but it can serve as a surface catalyser in hydrogen peroxide decomposition [21]. We chose this stable material for comparative measurements supposing that it had the same effect in all experiments.…”
Section: Methodsmentioning
confidence: 99%